2017
DOI: 10.5137/1019-5149.jtn.21588-17.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sinonasal complications of microscopic and endoscopic approaches for transsphenoidal hypophyseal surgery; prospective study

Abstract: There were no statistically significant differences in sinonasal complications (e.g. synechiae, anosmia, deformity, and sinusitis) between the two groups. Although the perforation rate (especially for perforations in the middle portion of the septum) was statistically greater in Group 1 than in Group 2, the hyposmia rate was statistically greater in Group 2 than in Group 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
1
5
0
1
Order By: Relevance
“…Regarding epistaxis, the rate was 3.8% in our study, while in other series by de Divitiis et al [ 7 ] and Frank et al [ 11 ], the epistaxis rates were 1.7% and 0.7%, respectively. Endoscopic transsphenoidal surgery is reported to be superior to microscopic transsphenoidal surgery in terms of sino-nasal complications, concerning the visual contribution of the endoscope at all stages of the surgery, the reduction of blind instrument maneuvers, and the absence of a speculum [ 15 , 24 , 30 ]. Surgical experience and collaboration with otolaryngologist specialists were shown to reduce epistaxis rates [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding epistaxis, the rate was 3.8% in our study, while in other series by de Divitiis et al [ 7 ] and Frank et al [ 11 ], the epistaxis rates were 1.7% and 0.7%, respectively. Endoscopic transsphenoidal surgery is reported to be superior to microscopic transsphenoidal surgery in terms of sino-nasal complications, concerning the visual contribution of the endoscope at all stages of the surgery, the reduction of blind instrument maneuvers, and the absence of a speculum [ 15 , 24 , 30 ]. Surgical experience and collaboration with otolaryngologist specialists were shown to reduce epistaxis rates [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic transsphenoidal surgery is reported to be superior to microscopic transsphenoidal surgery in terms of sino-nasal complications, concerning the visual contribution of the endoscope at all stages of the surgery, the reduction of blind instrument maneuvers, and the absence of a speculum [ 15 , 24 , 30 ]. Surgical experience and collaboration with otolaryngologist specialists were shown to reduce epistaxis rates [ 24 ]. Since we did not receive close support from an otolaryngologist clinic, except in the first 15 cases in our study, we believe that this resulted in higher rates of epistaxis in patients at the beginning of our surgical experience, compared to the reported rates in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Hipofiz cerrahisinde endoskopik ve mikroskobik tekniğin sinonazal yaşam kalitesine etkisini karşılaştıran prospektif bir çalışmada, postoperatif 3. aydaki sinonazal yaşam kalitesi skorları endoskopik teknikte istatiksel olarak anlamlı yüksek bulunmuştur (19,20) . Endoskopik cerrahide spekulum gerekmemesi hasta konforuna katkı sağlamakta, ameliyat sonrası daha az ağrı ile karşılaşılmakta, burun tamponu kullanma gereksinimini azaltmakta ve cerrahi sırasında anatomik yapıların daha iyi tanımlanabilmesine ve daha geniş açı ile yaklaşıma olanak sağlayabilmektedir (17) .…”
Section: Cerrahi Prosedürunclassified
“…5,6 According to the literature, 18% to 38% of patients reported a decreased subjective sense of smell at 3 months after undergoing endoscopic transsphenoidal hypophysectomy (ETSH); about 10% of the hyposmia was moderate or severe. [7][8][9] Meanwhile, objective psychophysical testing revealed a similar 8% to 35% incidence of postoperative moderate-to-severe hyposmia, a wide range that underscored the inconsistency of the methods used and results reported in previous studies. [10][11][12] A recent meta-analysis of studies that used only validated objective measures of olfaction revealed no differences in olfaction before and after the procedure but also highlighted the high heterogeneity of the included studies.…”
mentioning
confidence: 92%